Criminal Liability Committed By Debt Collectors Due To Violence In Arrears - Ismiyati Usman (Universitas Negeri Gorontalo, 2019)
This study aims to find out how Criminal Liability is Committed By Debt Collectors Due to Violence In Arrears. The type of research used in this research is the normative approach used in this study consists of two, namely the Statue Approach and conceptual approach. Analysis of legal materials in this study uses systematic interpretation methods. The results of this study show that the legal consequences of violence committed by debt collectors against customers who make installment leasing are the result of actions that are not by the law so that all parties involved receive the impact of the violence committed by the debt collector. However, the element of error becomes the determinant of who can be held criminally accountable. Legal entities or corporations that can be held criminally liable for violence committed by debt collectors against customers due to the establishment of leasing installments, through the theory of identification, strict liability (absolute accountability), and vicarious liability (substitute criminal liability), if there is an element of error, both intentional and void from the financing company itself. The Financial Services Authority should tighten supervision of financing companies that use debt collector services to minimize inequality in the use of debt collector services.